Secretome Prediction of Two M. tuberculosis Clinical Isolates Reveals Their High Antigenic Density and Potential Drug Targets - Cornejo-Granados, Fernanda; Zatarain-Barrón, Zyanya L.; Cantu-Robles, Vito A.; Mendoza-Vargas, Alfredo; Molina-Romero, Camilo; Sánchez, Filiberto; Del Pozo-Yauner, Luis; Hernández-Pando, Rogelio; Ochoa-Leyva, Adrián (Frontiers in Microbiology, 2017)
The Excreted/Secreted (ES) proteins play important roles during Mycobacterium tuberculosis invasion, virulence, and survival inside the host and they are a major source of immunogenic proteins. However, the molecular complexity of the bacillus cell wall has made difficult the experimental isolation of the total bacterial ES proteins. Here, we reported the genomes of two Beijing genotype M. tuberculosis clinical isolates obtained from patients from Vietnam (isolate 46) and South Africa (isolate 48). We developed a bioinformatics pipeline to predict their secretomes and observed that ~12% of the genome-encoded proteins are ES, being PE, PE-PGRS, and PPE the most abundant protein domains. Additionally, the Gene Ontology, KEGG pathways and Enzyme Classes annotations supported the expected functions for the secretomes. The ~70% of an experimental secretome compiled from literature was contained in our predicted secretomes, while only the 34–41% of the experimental secretome was contained in the two previously reported secretomes for H37Rv. These results suggest that our bioinformatics pipeline is better to predict a more complete set of ES proteins in M. tuberculosis genomes. The predicted ES proteins showed a significant higher antigenic density measured by Abundance of Antigenic Regions (AAR) value than the non-ES proteins and also compared to random constructed secretomes. Additionally, we predicted the secretomes for H37Rv, H37Ra, and two M. bovis BCG genomes. The antigenic density for BGG and for isolates 46 and 48 was higher than the observed for H37Rv and H37Ra secretomes. In addition, two sets of immunogenic proteins previously reported in patients with tuberculosis also showed a high antigenic density. Interestingly, mice infected with isolate 46 showed a significant lower survival rate than the ones infected with isolate 48 and both survival rates were lower than the one previously reported for the H37Rv in the same murine model. Finally, after a druggability analysis of the secretomes, we found potential drug targets such as cytochrome P450, thiol peroxidase, the Ag85C, and Ribonucleoside Reductase in the secreted proteins that could be used as drug targets for novel treatments against Tuberculosis.